The effect of tertiary treated wastewater on fish growth and health : laboratory-scale experiment with Poecilia reticulata (guppy) - Zaibel, Inbal (2019)
Treated wastewater (TWW) constitutes a sustainable water resource and has been used for fish culture in some countries around the world, although there are no comprehensive data on the effect of TWW on fish growth and health in the context of aquaculture production. Our objectives were to examine how fish culture in TWW affected fish growth and fitness, as well as compliance with the international standards for safe consumption. Guppy (Poecilia reticulata) fingerlings were reared in 0%, 50% and 100% tertiary TWW (TTWW), from the age of five days, for a period of four months. In water analyses, 33 out of 67 tested organic micropollutants (OMPs) were detected in the TTWW samples at least once, at concentrations that are typically reported in domestic TTWW. Fish survival ranged between 77–80% and did not differ between treatment groups. Fish growth and mortality following challenge infection with Tetrahymena sp. (which ranged between 64–68%), were similar among treatment groups. Of tested immunological parameters, lysozyme and anti-protease was similar among treatments while complement activity was highest in the 50% TTWW-reared fish. No abnormalities were observed in the histopathological analysis. Levels of heavy metals, polychlorinated-biphenyls (PCBs) and organochlorines (OCs) in fish were below the detection limit and below the Food and Agriculture Organization of the United Nations (FAO) and the European Union EU maximal permitted levels in food fish. Results suggest that the yield of fish grown in TTWW is potentially similar to that in freshwater, and the produced fish comply with the standards of consumer safety. The results are in line with previous studies that examined the feasibility of TWW-fed aquaculture.